Mediterranean Basin Wetlands as a Vertebral Axis of the Territory: Relationships with Roman Roads and Contemporary Livestock Trails. Issue 1 (1st March 2019) - Fornell Muñoz, Alejandro; Guerrero, Francisco
Abstract : Within the framework of the new environmental history, this article focuses on the interaction between historical human societies and a given natural environment. Specifically, we study the spatial relationships between wetlands, Roman roads, and contemporary livestock trails, with the aim of verifying the role of wetlands as a support of territory planning since antiquity to the present. The documentation used includes geographical and ecological manuscripts together with ancient sources (texts, archaeology). Our results demonstrate an overlapping that remarks the importance of wetlands in the study area's territorial ordering during various historical moments. This result also opens the possibility of applying this reality to others parts of the Mediterranean region with the same climatological conditions and a similar history. The clear heritage value of the wetlands are compelling enough to take the necessary protection measures for their conservation in the face of the growing threat of their deterioration and disappearance.